2010
DOI: 10.1093/jac/dkq356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of e-Bug, an educational pack, teaching about prudent antibiotic use and hygiene, in the Czech Republic, France and England

Abstract: Although a success, modifications are required in both packs to further improve student knowledge and make the packs more appealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 19 publications
4
62
0
1
Order By: Relevance
“…Failure to obtain a knowledge retention questionnaire from participants' means we have no information as to whether or not knowledge change via the intervention has lasting effects, however our previous work with the younger age group suggests that knowledge improvement gained via interactive activities is lasting [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Failure to obtain a knowledge retention questionnaire from participants' means we have no information as to whether or not knowledge change via the intervention has lasting effects, however our previous work with the younger age group suggests that knowledge improvement gained via interactive activities is lasting [21].…”
Section: Discussionmentioning
confidence: 99%
“…The large improvement in children's knowledge may be attributed to the interactive and group learning experience which children prefer [21]. Children are the largest consumers of antibiotics but research has suggested that their knowledge of medicine is poor, despite the fact that they have more control in medicine use than most adults would predict [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pregame questionnaire asked 7 simple multiple-choice questions adapted from a previous e-Bug evaluation [22]. Pupils’ responses were recorded as right or wrong.…”
Section: Methodsmentioning
confidence: 99%
“…An excellent example of an educational site is the e-bug © project (www.e-bug.eu), which was launched in 2006 with the aim of educating children and teenagers about microbiology, hygiene and the spread, treatment and prevention of infectious diseases. It has separate access for junior students, senior students and teachers, contains various interactive sections, ranging from disease fact-sheets to games and quizzes, 41 and has proved efficacious in improving students’ knowledge 42 . Specifically, the most downloaded resource document in 2009 was a swine flu fact-sheet 43 .…”
Section: Health Literacy and Ictmentioning
confidence: 99%